SPATIAL DISTRIBUTION AND DENSITY OF TERMITE MOUNDS IN A PROTECTED HABITAT IN THE SOUTH OF COTE D’IVOIRE: CASE OF NATIONAL FLORISTIC CENTER (CNF) OF UFHB OF ABIDJAN - Jean-Pierre, Boga; Moise, Akpesse Akpa Alexandre; Mauricette, Ouali-N’goran San-Whouli; Sylvain, Trabi Crolaud; Philippe, Kouassi Kouassi; Yao, Tano; Ahoua, Yapi (European Scientific Journal, ESJ, 2015)
The spatial distribution and termite mounds density and their activity were studies in order to assess to the biological restoration level in a protected area, knowing that termites are considered as tropical ecosystem engineers. The CNF area was subdivided into 4 sectors (SW, SE, NW and NE). In every sector of 1.75 ha, 20 transects (5 m x 100 m) were sampled. Termite nests were counted. Their dimensions and geographical coordinates were recorded. The superposition of spatial distribution maps of the 3 types of termite mounds showed an impressive abundance of termite mounds in all CNF area. In total, there were recorded 165 termite mounds. They were composed of 119 epigeal termite mounds and 46 tree-dwelling termite mounds. The average density of the 3 types of termite mounds on the CNF area was 23.57 mounds/ha with a dispersion coefficient of 0.07. The average density of Macrotermes mounds (8.99 mounds/ha), Cubitermes mounds (8.00 mounds/ha) and that of arboreal termite mounds (6.57 mounds/ha), with respective dispersion coefficient of 0.10, 0.08 and 0.07, showed no significant difference between them (p> 0.05). The epigeal termite mounds moved 297.42 tons of soil to build their nests. Macrotermes only, moved 297.03 tons (99.87%) of soil. On the CNF area, Macrotermes mounds have occupied a base area of 373.3 m2 and a volume of 264.99 m3. Cubitermes mounds covered a total base area of 2.08 m2 and a volume of 0.42 m3. These results are the reflection of a strong activity of the termite colonies, gradually restored in this protected habitat for 51 years.